GENETIC VARIABILITY AND CHARACTER ASSOCIATION OVER ENVIRONMENT IN PEARL MILLET [PENNISETUM GLAUCUM (L.) R. BR.] UNDER DRYLAND CONDITIONS OF GUJARAT - J. S. DAPKE; D. S. SHAH; G.N. PAWAR; V. M. DHEMBRE (The Bioscan, 2014)
To assess the genetic variability and character association among the twenty advanced hybrids, twelve R line and twelve B lines of pearl millet were studied for ten quantitative traits. All the genotypes showed considerable amount of variation in their mean performances with respect to the characters studied, indicates presence of sufficient variability and scope for further selection and breeding superior and desirable genotypes. GCV played a major role for the expression of the traits. Grain yield/plant (55.5) had high GCV per cent followed by grain yield/earhead (48.6) biological yield/plant (46.0), Plant height (26.3), earhead length (20.5) Flag leaf area (19.8) harvest index (15.7) and number of effective tillers (13.8) in pooled environment. Heritability in narrow sense ranged from 65.0 (harvest index) to 95.0 (grain yield/plant) in pooled environment. High GA% observed for grain yield (111.5) coupled with high heritability (95.0), indicating the preponderance of the additive gene action. Grain yield had genotypically significant positive correlation with most of the characters under study viz. grain yield/earhead (0.976), biological yield/plant (0.986), plant height (0.814), harvest index (0.666), earhead length (0.556) and number of effective tillers/plant (0.732) indicating any increase in these traits will increase the yield. The path analysis revealed high positive direct effect on grain yield per plant with respect to grain yield per earhead, biological yield per plant, number of effective tillers, days to 50 per cent flowering, earhead length and harvest index indicating importance of these characters, which can be strategically used to improve the yield of pearl millet.